The Urgency of Agricultural Insurance in Legal Protection Efforts for Farmers - Astuti, Hesti Dwi (KnE Social Sciences, 2023)
Climate change is a global threat with profound effects on agricultural businesses, such as floods, droughts, crop failures, and harvest losses. This study aims to analyze the urgency of agricultural insurance as a means of protecting farmers from the risks of crop failure resulting from climate change and its related disasters. The primary goal is to determine the importance of agricultural insurance for farmers. The research adopts a normative juridical approach with a descriptive research design, utilizing secondary data and qualitative analysis. The findings demonstrate that agricultural insurance plays a crucial role in mitigating the adverse impacts of climate change and unpredictable derivative disasters. It serves as a solution for farmers to cope with losses arising from the risk of crop failure. Despite its significance, the implementation of agricultural insurance programs is not fully optimized, mainly due to low awareness among farmers regarding insurance benefits. To address this issue, government intervention is necessary to raise awareness about the importance of agricultural insurance. By doing so, farmers’ rights can be protected, and their mindset can shift towards adopting modern agricultural practices. Keywords: farmers, insurance, legal protection